PENGARUH KEAKTIFAN MENGIKUTI PUJA BAKTI DAN PRAKTIK MEDITASI TERHADAP TINGKAT RELIGIUSITAS UMAT BUDDHA DI VIHARA TRI DHAMMA LOKA, KABUPATEN GROBOGAN - Ferawati Vimala Dewi; Mujianto; Mettadewi Wong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low consistency of some Buddhists in participating in puja bakti services and meditation practices amid the increasing complexity of modern life. Puja bakti and meditation are important spiritual activities that contribute to the development of Buddhist religiosity by strengthening faith, deepening spiritual understanding, and encouraging the application of Dhamma values in daily life. However, some Buddhists remain less active in these activities, resulting in a suboptimal level of religiosity. Therefore, this study aimed to analyze the influence of participation in puja bakti services and meditation practices on the religiosity of Buddhists at Tri Dhamma Loka Vihara, Grobogan Regency, both partially and simultaneously. This study employed a quantitative approach using a survey method. The population consisted of 125 Buddhists at Tri Dhamma Loka Vihara, Grobogan Regency. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS, including classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results revealed that participation in puja bakti services had a positive and significant effect on Buddhist religiosity (t = 4.215; p < 0.05). Meditation practice also had a positive and significant effect on religiosity (t = 5.103; p < 0.05). Simultaneously, both variables significantly influenced the religiosity of Buddhists (F = 38.762; p < 0.05). The Adjusted R Square value of 0.624 indicates that participation in puja bakti services and meditation practices contributed 62.4% to the religiosity of Buddhists, while the remaining 37.6% was influenced by other factors outside the scope of this study. These findings confirm the importance of puja bakti services and meditation practices in enhancing Buddhist religiosity.